Labia and Lingua Histopathology of Bali Cow (Bos sondaicus) on Hepatogenous Photosensitization Symptoms in Pakutatan Village, Jembrana, Bali - Mardika, Kadek; Setyawati, Iriani; Yulihastuti, Dwi Ariani (Advances in Tropical Biodiversity and Environmental Sciences, 2018)
Hepatogenous photosensitization is one of the ruminant diseases with symptoms of dermatitis or eczema of the skin accompanied by liver damage.  The disease is caused by the compounds of toxic lantadene A and lantadene B which are secondary metabolites of Lantana camara plant.  This research was carried out on January 2017. The material used in this study was preserved organs of the labia and lingua of dead three year old cow ( Bos sondaicus ).  Samples were taken from Pakutatan Village, Jembrana, Bali.  Identification of organ samples, histological preparation and histopathological examination were conducted at the Disease Investigation Center (DIC) 6, Denpasar, Bali.  The preparation of labia and lingua samples used the paraffin method with Hematoxylin and Eosin staining.  The tissue structural damages found were necrosis, inflammatory cell infiltration, congestion and tissue bleeding.  The data obtained were analyzed statistically by One Way Anova test with a confidence level of 95%.  Based on the results,  dead Bali cow which consumed a large numbers of Lantana camara plants showed that the highest number of cell damage was at the picnotic stage of cell necrosis (cell death) in the labia organ significantly (P<0.005), while the highest bacterial invasion was found in the labia organ with an average percentage of 12.40%.